A 27-Year-Old Severely Immunosuppressed Female with Misleading Clinical Features of Disseminated Cutaneous Sporotrichosis. (4th January 2016) - Patel, Atiyah; Mudenda, Victor; Lakhi, Shabir; Ngalamika, Owen
Abstract : Sporotrichosis is a subacute or chronic granulomatous mycosis caused by fungus of the Sporothrix schenckii complex. It is considered to be a rare condition in most parts of the world. It mostly causes cutaneous infection but can also cause multisystemic disease. Unlike most deep cutaneous mycoses which have a primary pulmonary focus, it is usually caused by direct inoculation of the fungus into the skin causing a classical linear, lymphocutaneous nodular eruption. However, atypical presentations of the condition can occur especially in immunosuppressed individuals. We report the case of a severely immunosuppressed female who presented with disseminated cutaneous sporotrichosis which was initially diagnosed and treated as disseminated cutaneous Kaposi's sarcoma.